Novel synthetic coumarins that targets NF-κB in Hepatocellular carcinoma. Issue 4 (15th February 2015) - Neelgundmath, Mahabaleshwaraiah; Dinesh, Koragere Rajashekar; Mohan, Chakrabhavi Dhananjaya; Li, Feng; Dai, Xiaoyun; Siveen, Kodappully Sivaraman; Paricharak, Shardul; Mason, Daniel J.; Fuchs, Julian E.; Sethi, Gautam; Bender, Andreas; Rangappa, Kanchugarakoppal S.; et al.
Graphical abstract